2017
DOI: 10.1002/aet2.10040
|View full text |Cite
|
Sign up to set email alerts
|

A Ten‐year Program Evaluation of an Emergency Medicine Scholarly Track in Education Using a Qualitative Approach

Abstract: Background: Residency scholarly tracks have allowed training programs to better prepare residents for a future

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(10 reference statements)
2
3
0
Order By: Relevance
“…Our study indicated that medical education registrars seek formal knowledge and skills in the role, congruent with reviews of other similar programmes, but reflect on broader issues after the training post and subsequent experience.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Our study indicated that medical education registrars seek formal knowledge and skills in the role, congruent with reviews of other similar programmes, but reflect on broader issues after the training post and subsequent experience.…”
Section: Discussionsupporting
confidence: 75%
“…Our respondents learning trajectory, and developing identities as both clinician and clinical educator, were strongly influenced by organisational culture, and whether a CoP was perceived. This parallels the findings of a 10 year programme evaluation of a US‐based emergency medicine ‘scholarly track in education’, in which opportunities for leadership and collaboration were identified as key themes by stakeholders …”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations